2019
DOI: 10.3389/fnins.2019.00470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Voluntary Wheel Running During Pregnancy on Adult Hippocampal Neurogenesis, Temporal Order Memory, and Depression-Like Behavior in Adult Female and Male Offspring

Abstract: Research suggests that maternal exercise in pregnancy may have beneficial effects on the brain function of offspring. This study sought to determine if voluntary wheel running during pregnancy improves depression-like behavior, temporal order memory, and hippocampal neurogenesis in both female and male offspring mice. Pregnant mice were allowed to run voluntarily by introducing running wheels into the housing cages throughout the gestational period. Male and female mice offspring at the age of 8- to 9-week-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Immunostaining was performed by the free-floating method, as previously performed [ 85 ]. For BrdU staining, the antigens were retrieved in the citric acid buffer (pH 6.0) at 95 °C for 15 min, then denatured in 2 N HCl for 30 min and neutralized by 0.1 M borate buffer (pH 8.5) for 15 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Immunostaining was performed by the free-floating method, as previously performed [ 85 ]. For BrdU staining, the antigens were retrieved in the citric acid buffer (pH 6.0) at 95 °C for 15 min, then denatured in 2 N HCl for 30 min and neutralized by 0.1 M borate buffer (pH 8.5) for 15 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…However, many other studies reported no sex differences in these behaviors (e.g., [57]) and some have reported decreased anxiety-and depressive-like behaviors in male rats [58]. In mice, sex differences in anxiety-and depressive-like behaviors are inconsistently reported [59,60], and also similar to rats, the appearance of sex differences varies by genetic background as reflected by strain differences [59,61,62]. Sprague Dawley rats, for example, exhibit stable sex differences in immobility measures in a modified and extended version of the forced swim test, whereas a lack of sex differences was present in Long Evans rats across tests [63].…”
Section: Sex Differences In Anxiety/depressive-like Behaviors In Humamentioning
confidence: 99%
“…An animal study on rats investigated the effects of maternal physical activity on gene expression of the neurotrophic factors, and upregulation was found in placenta of the very active mothers (Fragoso et al, 2020). Additionally, other studies found voluntary exercise during pregnancy significantly increased the level of neurotrophic factors protein in hippocampus of rat pups; and female offspring born to pregnant mice with voluntary running wheels showed enhanced cell proliferation in the dorsal hippocampus (Akhavan et al, 2013;Yau et al, 2019). These animal studies suggest that maternal physical activity during pregnancy may promote fetal brain development in a biological point of view.…”
Section: Discussionmentioning
confidence: 99%